Analisis Penentuan Harga Jual Terhadap Peningkatan Penjualan Pada Sentra Tahu Berkah Jaya Metro Barat - Dewi Astuti; Nurul Hakiki; Tri Aulia; Umi Salimah; Carmidah Carmidah (CiDEA Journal, 2023)
This study aims to analyze the determination of selling prices to increase sales at Sentra Tahu Berkah Jaya. Sentral Tahu Berkah Jaya is one of the businesses engaged in the production of tofu which has been established since 2003 located in Ganjar Agung, West Metro Metro City. The type of research used is case study research with observation and interview methods. The data processed is data in the form of basic price records such as raw material costs, labor costs and factory overhead costs. While the data analysis techniques used in the research are (1) data collection, (2) data reduction, (3) data presentation, (4) conclusion making. The results of the study show that the tofu production process has a major effect on determining the selling price.